Organometallic Chemistry : Vol. 37 - Fairlamb, I.; LyNAm, Jason M. (Cambridge : RSC pub., 2011)
Annotation Organometallic chemistry is an interdisciplinary science which continues to grow at a rapid pace. Although there is continued interest in synthetic and structural studies, the last decade has seen a growing interest in the potential of organometallic chemistry to provide answers to problems in catalysis, synthetic organic chemistry and also in the development of new materials. Each volume in the series is published either annually or biennially and is a superb reference point for researchers.
Includes bibliographical references and index.
Keywords: Organometallic Chemistry